Activated Braf induces esophageal dilation and gastric epithelial hyperplasia in mice. (14th September 2017) - Inoue, Shin-Ichi; Takahara, Shingo; Yoshikawa, Takeo; Niihori, Tetsuya; Yanai, Kazuhiko; Matsubara, Yoichi; Aoki, Yoko
Abstract: Germline mutations in BRAF are a major cause of cardio-facio-cutaneous (CFC) syndrome, which is characterized by heart defects, characteristic craniofacial dysmorphology and dermatologic abnormalities. Patients with CFC syndrome also commonly show gastrointestinal dysfunction, including feeding and swallowing difficulties and gastroesophageal reflux. We have previously found that knock-in mice expressing a Braf Q241R mutation exhibit CFC syndrome-related phenotypes, such as growth retardation, craniofacial dysmorphisms, congenital heart defects and learning deficits. However, it remains unclear whether Braf Q241R /+ mice exhibit gastrointestinal dysfunction. Here, we report that Braf Q241R /+ mice have neonatal feeding difficulties and esophageal dilation. The esophagus tissues from Braf Q241R /+ mice displayed incomplete replacement of smooth muscle with skeletal muscle and decreased contraction. Furthermore, the Braf Q241R /+ mice showed hyperkeratosis and a thickened muscle layer in the forestomach. Treatment with MEK inhibitors ameliorated the growth retardation, esophageal dilation, hyperkeratosis and thickened muscle layer in the forestomach in Braf Q241R /+ mice. The esophageal dilation with aberrant skeletal-smooth muscle boundary in Braf Q241R /+ mice were recovered after treatment with the histone H3K27 demethylase inhibitor GSK-J4. Our results provide clues to elucidate the pathogenesis and possible treatment of gastrointestinal dysfunction and failure to thrive in patients with CFC syndrome.